Diskursus Sains dalam Kurikulum Pendidikan Agama Islam di Sekolah dan Madrasah Era Digital - Firman Mansir (Kamaya: Jurnal Ilmu Agama, 2020)
The changes in curriculum and everything in between such as development of Islamic education, science, development innovation, change and others are inevitability which generate new challenges in the field. Facing this reality, all element of society expects that the role of Islamic religious education which indeed has taught moral and spiritual value. Therefore the urgency of Islamic religious education in providing teachings or guidelines for social activities becomes a very urgent need. In line with the statement, we need an educators who have creativity and innovation to be able to develop learning well and professionally. No matter how good the curriculum design is, if the delivery is not good, an effective learning will certainly not work. Scientific based learning implementation in Islamic education must be conducted to face dynamic things in educational world including the digital industry development